2020
DOI: 10.1186/s12967-020-02380-2
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the clinical use of adipose-derived mesenchymal stem cells for COVID-19 patients

Abstract: In late 2019, a novel coronavirus (SARS-CoV-2) emerged in Wuhan, capital city of Hubei province in China. Cases of SARS-CoV-2 infection quickly grew by several thousand per day. Less than 100 days later, the World Health Organization declared that the rapidly spreading viral outbreak had become a global pandemic. Coronavirus disease 2019 (COVID-19) is typically associated with fever and respiratory symptoms. It often progresses to severe respiratory distress and multi-organ failure which carry a high mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 233 publications
4
99
0
6
Order By: Relevance
“…These cytokines are known to be elevated as a result of cytokine storm due to the activation of innate immune cells, including macrophages during acute viral and bacterial infection (e.g., SARS-COV-2 infection (21,22), sepsis (23,24)), and BM and CT-MSCs (both OOT and CR products) may mitigate the hyperinflammation by inhibiting the cytokine response of macrophages (25,26). In T cell proliferation assay, OOT MSCs showed very low or no suppression as compared to CR MSCs for both BM and CT MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are known to be elevated as a result of cytokine storm due to the activation of innate immune cells, including macrophages during acute viral and bacterial infection (e.g., SARS-COV-2 infection (21,22), sepsis (23,24)), and BM and CT-MSCs (both OOT and CR products) may mitigate the hyperinflammation by inhibiting the cytokine response of macrophages (25,26). In T cell proliferation assay, OOT MSCs showed very low or no suppression as compared to CR MSCs for both BM and CT MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of serious complications caused by the improper application of MSCs in the past [28]. Donor-specific antibodies have been observed in 19-34% of patients receiving allogeneic AD-MSCs infusion suggesting that a cellular response can occur [29]. On the other hand, no clinical immune reactions have been seen in studies that have used intravenous AD-MSCs (1×10 6 ASCs/kg) as reported in a recent review [29].…”
Section: Safety Of Mscs Treatmentmentioning
confidence: 99%
“…These results provide important insights into A-Se-MiRs function and could suggest their use as anti-viral. On the basis of the mentioned above concepts, ASCs treatments may reduce the demand for critical hospital resources [29].…”
Section: Ad-mscs and Their A-se-mirs As Cellular Weapons In The Inflamentioning
confidence: 99%
See 1 more Smart Citation
“…EV biochemistry varies according to composition and cell source (41). EVs can carry membrane and cytosolic proteins, transcription factors, DNA, coding and non-coding RNAs and various signal transduction molecules (5,21,38,42), acting on both physiological and pathological events, e.g., modulating the inflammatory response (2,14). EVs also carry different cytokines and growth factors, such as interleukin (IL)-6 and IL-10, transforming growth factor (TGF)-β, and hepatocyte growth factor (HGF) (43).…”
Section: Rationale For Using Extracellular Vesicles In Covid-19mentioning
confidence: 99%